Contextual factors influencing decision making: Perceptions of professional soccer players. (July 2018) - Levi, Hannah R.; Jackson, Robin C.
Abstract: Objectives: This study sought to explore highly-skilled soccer players' perceptions of how contextual factors influence their decision making during matches. Design: A qualitative design was used in which individual semi-structured interviews were conducted with eight professional male soccer players aged between 18 and 22 years. Method: An interview schedule was designed to explore the perceived influence of a range of situational factors on decision making during matches. The interviews were recorded and transcribed verbatim. The data were analysed via an inductive thematic analysis. Results: Seven themes were identified from the data. The four dynamic contextual themes were: (a) personal performance, (b) score status, (c) momentum, and (d) external/coach instructions. The three static contextual themes were: (a) match importance, (b) personal pressures, and (c) preparation. Conclusions: The results highlight the importance of considering the dynamic and static context within which highly-skilled soccer players make decisions. Highlights: Semi-structured interviews were conducted with eight professional soccer players. Static and dynamic contextual themes were perceived to influence decision making. Dynamic themes related to performance, score status, momentum, and communication. Static themes related to match importance, perceived pressure, and preparation.